Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1074/jbc.274.26.18785
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HHR23A as a Substrate for E6-associated Protein-mediated Ubiquitination

Abstract: The human papilloma virus E6-associated protein (E6AP) functions as a ubiquitin protein ligase (E3) in the E6-mediated ubiquitination of p53. E6AP is also an E3 in the absence of E6, but its normal cellular substrates have not yet been identified. Here we report the identification of HHR23A, one of the human homologues of the yeast DNA repair protein Rad23, as an E6-independent target of E6AP. HHR23A binds E6AP and is ubiquitinated in vitro in an E6AP-dependent manner. Ubiquitinated forms of endogenous HHR23A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(137 citation statements)
references
References 52 publications
(71 reference statements)
4
131
2
Order By: Relevance
“…It is also strange that CAL was not affected by siE6AP, which was shown to effect hScrib and p53 activation. The level of endogenous HHR23A, an E6-independent target of E6AP was also examined (Kumar et al, 1999), but prominent changes were not detected (data not shown). The inefficiency of siE6AP might be because the silencing effect of siE6AP was not sufficient to affect the steady-state levels of CAL and HHR23A.…”
Section: Gapdh Was Used As a Control (Bottom Panel) (B)mentioning
confidence: 99%
“…It is also strange that CAL was not affected by siE6AP, which was shown to effect hScrib and p53 activation. The level of endogenous HHR23A, an E6-independent target of E6AP was also examined (Kumar et al, 1999), but prominent changes were not detected (data not shown). The inefficiency of siE6AP might be because the silencing effect of siE6AP was not sufficient to affect the steady-state levels of CAL and HHR23A.…”
Section: Gapdh Was Used As a Control (Bottom Panel) (B)mentioning
confidence: 99%
“…As E6AP is involved in the ubiquitination of proteins associated with key cellular functions, [3][4][5][6][7] to examine the biological implications of its suppression in HPV-positive cells, we observed their individual DNA content by FACS analysis. Under normal growth conditions, there was no observable change in the cell-cycle profile associated with ribozyme-mediated reduction in E6AP.…”
Section: E6ap Gene Suppression and Apoptosismentioning
confidence: 99%
“…2 It has since been shown that E6AP acts as an E3 in the ubiquitin-dependent proteolysis of various other cellular proteins, both in the presence and absence of HPV E6. [3][4][5][6][7] E6AP was also the founding member of a family of structurally related E3s carrying a carboxyl terminus that is highly conserved among various organisms, termed the hect domain (homology to E6AP C terminus). 8 Besides its protein ligase function, E6AP…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a screen of both fetal brain and HeLa cell cDNA libraries, several known E6/ E6-AP interactors were identified, including p53, HHR23A (human homolog of rad23), and a homolog of the E6TP1 gene (Unigene Hs. 406879; Scheffner et al 1993;Gao et al 1999;Kumar et al 1999). In addition, a new E6/E6-AP target protein identified in the screen was NFX1 (nuclear factor binds to the X1 box), a transcriptional repressor of MHC class II genes (Song et al 1994).…”
Section: A New Target Of E6/e6-apmentioning
confidence: 99%